Quercetin in semen extender improves frozen-thawed spermatozoa quality and in-vivo fertility in crossbred Kamori goats - Batool, Iqra; Fayyaz, Muhammad Hammad; Hameed, Amjad; Andrabi, Syed Murtaza Hassan; Kausar, Rehana; Shahzad, Muhammad; Mubashir, Yasin; Omur, Ali Dogan; Murtaza, Ghulam; Ditta, Allah; Hussain, Tarique (Frontiers in Veterinary Science, 2024)
This study investigated the antioxidant effect of quercetin-treated semen on frozen–thawed spermatozoa quality and in-vivo fertility in crossbred Kamori goats. In total, 32 ejaculates from four fertile bucks were diluted in Tris-based egg yolk extender with varying levels of quercetin (0, 1, 5, 10, and 15 μM). Qualified semen samples were pooled and frozen in French straws. The results revealed that the addition of quercetin in the semen extender increased (p < 0.05) frozen–thawed sperm total motility (TM), progressive motility (PM), rapid velocity (RV), average path velocity (VAP), straight line velocity (VSL), curvilinear velocity (VCL), and amplitude of lateral head (ALH) displacement in contrast to the control group. Quercetin supplementation had no effect on beat cross frequency (BCF), straightness (STR), and linearity (LIN) (p > 0.05). Quercetin showed significantly higher (p < 0.05) plasma membrane and acrosome integrity and viability (p < 0.05) of spermatozoa in contrast to the control group. Quercetin in the semen extender significantly increased (p < 0.05) superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), ascorbate peroxidase (APX), and total antioxidant capacity (TAC) levels while reduced (p < 0.05) the contents of total oxidant status (TOS) and malondialdehyde (MDA), which were in contrast to the control group. Ultrasound results revealed that 24 out of 30 (80%) goats were found pregnant when semen was treated with 5 μM quercetin while the control group showed 18 out of 30 (60%) animals were pregnant. Thus, the study concluded that 5 μM quercetin-treated semen was found to be efficient, showed increased antioxidant status, and reduced oxidant production, leading to improved spermatozoa quality and in-vivo fertility in goats.